A multi-scale analysis of basketball throw in virtual reality for tracking perceptual-motor expertise - Soltani, P.; Morice, A. H. P. (Scandinavian Journal of Medicine & Science in Sports, 2023)
To benefit from virtual reality (VR) as a complementary tool for training, coaches must determine the proper tools and variables for tracking sports performance. We explored the basketball shooting at several scales (basket-ball, ball-player, and player systems) by monitoring success-rate, and ball and body kinematics. We measured how these scales of analysis allowed tracking players' expertise and perceptual sensitivity to basket distance. Experienced and novice players were instructed to naturally throw and swish an instrumented ball in a stereoscopically rendered virtual basket. We challenged their perceptual-motor systems by manipulating the distance of the virtual basket while keeping the surrounding environment unchanged. The success-rate accounted for the players' shooting adjustments to the manipulation of basket distance and allowed tracking their expertise. Ball kinematics also reflected the manipulation of distance and allowed detecting gender, but did not reflect the players' expertise. Finally, body kinematics variables did not echo players' adjustments to the distance manipulation but reflected their expertise and gender. The results gained at each scale of analysis are discussed with regard to the simulator's construct, biomechanical, and psychological fidelity.